The idea of natural inequality and other essays - Beteille, Andre (Delhi ; New York : Oxford University Press, 2003)
In the Indian context.
Acknowledgements xiii
Introduction 1 (6)
The Idea of Natural Inequality 7 (28)
Homo Hierarchicus, Homo Equalis 35 (22)
Harmonic and Disharmonic Social Systems 57 (26)
The Backward Classes and the New Social Order 83 (47)
The Pursuit of Equality and the Indian University 130 (38)
Equality of Opportunity 168 (30)
Individualism and the Persistence of Collective Identities 198 (29)
Equality of Opportunity and the Equal Distribution of Benefits 227 (22)
Index
Includes bibliographical references and index.
Akbar Ali Khan Collection
Keywords: Equality; Social change; India -- Social conditions -- 1947-